2020
DOI: 10.1155/2020/8820881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Vascular Cognitive Impairment by Transcranial Magnetic Stimulation

Abstract: The exact relationship between cognitive functioning, cortical excitability, and synaptic plasticity in dementia is not completely understood. Vascular cognitive impairment (VCI) is deemed to be the most common cognitive disorder in the elderly since it encompasses any degree of vascular-based cognitive decline. In different cognitive disorders, including VCI, transcranial magnetic stimulation (TMS) can be exploited as a noninvasive tool able to evaluate in vivo the cortical excitability, the propension to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 159 publications
(190 reference statements)
1
55
0
1
Order By: Relevance
“…Finally, it is relevant to consider that the responder and non-responder groups classified following our tDCS-reconsolidation protocol, which entailed structural and functional neuroimaging differences, did not differ in baseline cognition, demographic variables, or clinical data. Thus, the stated imaging group differences are not likely explained by potential dissimilarities regarding vascular risk factors, which might have implied potential cortical excitability differences in response to NIBS, as previously reported (reviewed in Cantone et al, 2020 ).…”
Section: Discussionsupporting
confidence: 57%
“…Finally, it is relevant to consider that the responder and non-responder groups classified following our tDCS-reconsolidation protocol, which entailed structural and functional neuroimaging differences, did not differ in baseline cognition, demographic variables, or clinical data. Thus, the stated imaging group differences are not likely explained by potential dissimilarities regarding vascular risk factors, which might have implied potential cortical excitability differences in response to NIBS, as previously reported (reviewed in Cantone et al, 2020 ).…”
Section: Discussionsupporting
confidence: 57%
“…Some studies reported that the language understanding network, centered on the dominant hemisphere of the MTG, is the neural basis of the brain's language understanding function (41). As we know, language impairment is an important manifestation of vascular dementia (42). All of the brain regions mentioned above are part of the DMN, the main function of which is to extract the process of episodic memory, cognition, and emotion (43).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the language understanding network, centered on the dominant hemisphere of the MTG, is the neural basis of the brain's language understanding function ( 41 ). As we know, language impairment is an important manifestation of vascular dementia ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our understanding of the cellular and molecular mechanisms underlying distinct forms of synaptic plasticity, including metaplasticity, remains limited. Moreover, impaired synaptic plasticity, the so-called "maladaptive plasticity, " has been associated with the pathogenesis and trajectory of several brain diseases, including contributions to the dysfunctional remodeling of underlying neural networks (2)(3)(4)(5).…”
Section: Non-invasive Brain Stimulation In the Study And Modulation Of Metaplasticity In Neurological Disordersmentioning
confidence: 99%